The Status and Future Directions of Treatments for Polyglutamine Spinocerebellar Ataxia: A Bibliometric and Visual Analysis - Ding, Siyu; Peng, Linliu; Chen, Zhao; Dong, Mengyuan; Tang, Cuiling; Gong, Yiqing; He, Lang; Wu, Qi; Qiu, Rong; Jiang, Hong (Current Neuropharmacology, 2026)
BackgroundPolyglutamine (polyQ) spinocerebellar ataxias (SCA) are a group of autosomal dominant neurodegenerative disorders for which no effective treatments currently exist. These conditions impose a significant burden on patients, their families, and society. Consequently, the treatment of these disorders has attracted significant global interest.ObjectiveWe conducted this bibliometric analysis to identify the key research hotspots and predict the future research directions of this field.MethodsStudies relating to the treatment of polyQ SCA published from 1999 to 2024 were retrieved from the Web of Science Core Collection database. Relevant papers were selected using predefined inclusion and exclusion criteria. HistCite, VOSviewer, CiteSpace, and alluvial generator were used in the bibliometric analysis.ResultsOverall, 935 papers were included. The number of publications in this field showed a trend toward a fluctuating increase. The United States and the University of Coimbra were the leading countries and institutions, respectively, in terms of publication number. The two most productive and highly cited authors were Luis Pereira de Almeida and Patricia Maciel. The journals Cerebellum, Human Molecular Genetics, and Movement Disorders were considered the most influential based on the number of publications and citations. Furthermore, “new SCA types”, “Huntington’s disease”, “clinical trial”, “gene therapy”, “disease models,” and “Aggregation clearance therapy” emerged as current hotspots in this field, as revealed by the reference and keyword analyses.ConclusionThis study presents a systematic bibliometric analysis of research on the polyQ SCA treatment, which we hope will assist researchers in identifying the key topics and future research directions in this field.
Keywords: treatment